Intergenerational transmission of maternal behavioral traits in mice: involvement of the gut microbiota - Mogi, Kazutaka; Akiyama, Uruma; Futagawa, Natsumi; Tamura, Kanami; Kamiya, Mai; Mizuta, Mami; Yamaoka, Miku; Kamimura, Itsuka; Kuze-Arata, Sayaka; Kikusui, Takefumi (Frontiers in Neuroscience, 2024)
The matrilineal transmission of maternal behavior has been reported in several species. Studies, primarily on rats, have suggested the importance of postnatal experience and the involvement of epigenetic mechanisms in mediating these transmissions. This study aims to determine whether the matrilineal transmission of maternal behavior occurs in mice and whether the microbiota is involved.We first observed that early weaned (EW) female mice showed lower levels of maternal behavior, particularly licking/grooming (LG) of their own pups, than normally weaned (NW) female mice. This difference in maternal behavioral traits was also observed in the second generation, even though all mice were weaned normally. In the subsequent cross-fostering experiment, the levels of LG were influenced by the nurturing mother but not the biological mother. Finally, we transplanted the fecal microbiota from EW or NW mice into germ-free (GF) mice raising pups. The maternal behaviors that the pups exhibited toward their own offspring after growth were analyzed, and the levels of LG in GF mice colonized with microbiota from EW mice were lower than those in GF mice colonized with microbiota from NW mice. These results clearly indicate that, among maternal behavioral traits, LG is intergenerationally transmitted in mice and suggest that the vertical transmission of microbiota is involved in this process. This study demonstrates the universality of the intergenerational transmission of maternal behavioral traits and provides new insights into the role of microbiota.